Multiple emulsion templating of hybrid Ag/SiO2 capsules for antibacterial applications - Sousa, Filipa L.
Silver nanoparticles (NPs) encapsulated in amorphous silica shells are synthesized and evaluated for their antibacterial action using the Gram-negative Escherichia coli bacterium. These inorganic capsules are synthesized using a new approach that comprises the use of oil-in-water-in-oil (O/W/O) multiple emulsions to fabricate SiO2 capsules incorporating organically capped Ag NPs. This strategy is explored as a mean to promote the bioadhesion of the microorganisms to the silica rough surfaces while still keeping the system with a high surface area for the active metal. The results have shown that the hybrid capsules enable a slow release of cationic silver from the interior of the silica microsphere to the external medium probably through the pore channels in the shell. The antibacterial activity against E. coli is mainly determined by the Ag+ ion release rate, suggesting that these particulates can be employed as a robust system for prolonged used as an antimicrobial material.